A service evaluation comparing home-based testing to clinic-based testing for Chlamydia and gonorrhoea in Birmingham and Solihull. (September 2018) - Banerjee, Prita; Thorley, Nicola; Radcliffe, Keith
Home-based testing is an alternative, convenient and cost-effective method of testing for sexually transmitted infections compared to traditional clinic-based testing, in patients who are asymptomatic and, or, would otherwise feel stigmatised about attending sexual health clinics. The sexual health service in Birmingham and Solihull, called Umbrella, provides an online home-based testing service, which has been in operation since August 2015. The aim of this study was to evaluate the uptake and return rate of home-based testing kits and compare home-based testing to clinic-based testing in terms of diagnosis and treatment rates of Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (GC). Our study showed that home-based testing is a popular method of testing and relatively more popular amongst asymptomatic, young, heterosexual female and White patients than clinic-based testing, with a return rate of 48%. The diagnosis rates for CT/GC are comparable to patients who attend clinic for testing (8% vs. 10% in home-based and clinic-based groups, respectively, p < 0.001). The overall treatment rate was lower in the home-based compared to the clinic-based group (82% vs. 88%, p < 0.001). Umbrella will continue to provide this service within Birmingham and Solihull and aim to provide patients with alternative pathways for more convenient access to treatment.